Analyses of clinical outcomes after severe pelvic fractures: an international study. Issue 1 (21st November 2018) - Jung, Kyoungwon; Matsumoto, Shokei; Smith, Alan; Hwang, Kyungjin; Lee, John Cook-Jong; Coimbra, Raul
Abstract : Background: This study aimed to compare treatment outcomes between patients with severe pelvic fractures treated at a representative trauma center that was established in Korea since 2015 and matched cases treated in the USA. Methods: Two cohorts were selected from a single institution trauma database in South Korea (Ajou Trauma Data Bank (ATDB)) and the National Trauma Data Bank (NTDB) in the USA. Adult blunt trauma patients with a pelvic Abbreviated Injury Scale >3 were included. Patients were matched based on covariates that affect mortality rate using a 1:1 propensity score matching (PSM) approach. We compared differences in outcomes between the two groups, performed survival analysis for the cohort after PSM and identified factors associated with mortality. Lastly, we analyzed factors related to outcomes in the ATDB dataset comparing a period prior to the implementation of the trauma center according to US standards, an interim period and a postimplementation period. Results: After PSM, a total of 320 patients (160 in each cohort) were identified for comparison. Inhospital mortality was significantly higher in the ATDB cohort using χ 2 test, but it was not statistically significant when using Kaplan-Meier survival curves and Cox regression analysis. Moreover, the mortality rate was similar comparing the NTDB cohort to ATDB data reflecting the post-trauma center establishment period. Older age, lower systolic blood pressure (SBP) and Glasgow Coma Scale (GCS) at admission were factors associated with mortality. Discussion: Mortality rate after severe pelvic fractures was significantly associated with older age, lower SBP and GCS scores at admission. Efforts to establish a trauma center in South Korea led to improvement in outcomes, which are comparable to those in US centers. Level of evidence: Level IV.